Nachman Krochmal Guiding the Perplexed of the Modern Age - Harris, Jay (NYU Press, 1991)
"A well-organized and engaging read." Religious Studies Review The first in-depth look at...an important nineteenth century Jewish thinker and historian. Well-written [and] well- researched." The Jerusalem Post Magazine "A significant contribution to our understanding of the rise of modern Judaism in its East European manifestation." Choice Harris examines Nachman Krochmal's work, particularly as it aimed to guide Jews through the modern revolution in metaphysical and historical thinking, thus enabling them to commit themselves to Judaism without sacrificing intellectual integrity.